The Effect of Profitability, Leverage, Firm Size, and CSR on Stock Prices through Firm Value: Evidence from the Astra Group (2015–2023) - Rustiar, Rustiar; Rachman, Andry Arifian (Dinasti International Journal of Education Management and Social Science, 2025)
This study examines the effects of profitability, leverage, firm size, and corporate social responsibility (CSR) on stock prices through firm value in Astra Group companies listed on the Indonesia Stock Exchange during the 2015–2023 period. Using a quantitative panel data approach, the sample consists of five Astra Group companies, yielding 45 firm-year observations. The analysis employs the Fixed Effect Model (FEM) and mediation testing using the Sobel test. The results indicate that profitability, leverage, firm size, and CSR significantly influence firm value. In the stock price model, profitability and firm size exhibit significant effects, while leverage and CSR do not directly affect stock prices. Firm value plays a significant mediating role in all indirect relationships; however, the mediation effects of firm size and CSR are negative. This finding suggests that, within the Astra Group context, larger firm scale and higher CSR disclosure tend to reduce firm value, which subsequently weakens stock price performance. Such negative mediation reflects investor concerns regarding organisational complexity and the perception of CSR as a cost rather than an immediate value-creating activity in capital-intensive conglomerate sectors. The study implies that Astra Group companies should emphasise profitability-driven value creation, optimise organisational efficiency, and strategically align CSR initiatives with core business objectives to ensure positive market valuation. These findings contribute to the literature by highlighting the conditional and asymmetric role of firm value in transmitting fundamental performance to stock prices within diversified business groups.